A Chemical and Morphological Study of Cassava Peel: A Potential Waste as Coagulant Aid - Mohd-Asharuddin, Syazwani; Othman, Norzila; Mohd Zin, Nur Shaylinda; Tajarudin, Husnul Azan (EDP Sciences, 2017)
This study investigates the chemical and morphological characteristics of cassava peel (CP) biomass as a potential coagulant aid for turbidity, heavy metals and microbial removal. FE-SEM micrograph shown the surface of the CP samples was covered with smooth and globular in shaped of bound starch granules. FTIR spectra demonstrated that carboxyl and hydroxyl groups were present in abundance. Whereas analysis by XRF spectrometry indicated the CP samples contain Fe2O3 and Al2O3 which might contribute to its coagulation ability. The features of CP obtained from this study promotes the feasibility of CP to be further developed and studied to produce effective coagulant aid as sustainable alternative to reduce the usage of chemical coagulants.